A Brief Review of Chimera State in Empirical Brain Networks - Wang, Zhenhua; Liu, Zonghua (Frontiers in Physiology, 2020)
Understanding the human brain and its functions has always been an interesting problem. Recently, a significant progress on this problem has been achieved on the aspect of chimera state where a coexistence of synchronized and unsynchronized states can be sustained in identical oscillators. This counterintuitive phenomenon is closely related to the unihemispheric sleep in some birds and marine mammals and has gotten a hot attention in neural systems, except the systems of phase oscillators. This review will briefly summarize the main results of chimera state in neuronal systems and pay special attention to its applications in cerebral cortex, aiming to accelerate the study of chimera state in brain networks. Some outlooks are also discussed.